Unilateral palatally impacted canines: Evaluation of pulpal condition after surgical exposure and orthodontic alignment - Oskar Bauss; Stratos Vassis (Elsevier, 2022)
Objective: The study aimed to assess changes in the pulpal condition of unilateral palatally impacted canines during and after orthodontic alignment. In particular, the effects of patient's age at treatment start, treatment duration and angle of canine displacement were analyzed. Materials and methods: Clinical and radiographical examinations were conducted on a total of 66 patients with a unilateral palatally impacted canine, who previously underwent surgical exposure and were treated with multi-bracket appliances afterwards. After assessing the pulpal condition, the position of the canine was evaluated by analyzing the α-angle, d-distance and s-sector based on a modified version of the criteria proposed by Ericson and Kurol. A stepwise logistic regression was conducted to estimate the prognostic value of following parameters for the development of abnormal pulpal condition: alignment time, age at start of treatment, α-angle, d-distance and s-sector. Results: Occurrence of abnormal pulpal condition of the impacted canine was significantly correlated with patient's age at the start of orthodontic treatment (p < 0.001), canine inclination (p = 0.005), distance between the canine and the occlusal plane (p = 0.002) and impaction location between the upper jaw midline and the axis of the central incisor (p = 0.012). Conclusion: Beginning treatment of palatally impacted canines at an early age can avoid pulpal damage. Besides, inclination, distance to the occlusal plane and initial location require special orthodontic management to ensure pulpal protection.